(untitled) (Archaeologia Adriatica, 2022)
In the attire of many prehistoric, and later historic communities belt was an important functional, and also decorative element, that often had distinct symbolic function. Its form, selected material, craftsmanship and elaborate ornamental system could have communicated various messages regarding social, economic and symbolic aspects. In the area of the eastern Adriatic and its immediate hinterland, and in particular in the Liburnian region, during the last two centuries BCE, a specific type of belt buckles became a prominent and popular piece of attire. These were cast trapezoidal belt buckles featuring the central motif of a spear/arrow. Collection of extant finds of the mentioned type has been considerably augmented owing to systematic archaeological research of the Nadin necropolis where as many as 44 specimens have been found. They are joined by a certain number of unpublished finds kept in the collections of the Archaeological Museum in Zadar and the Šibenik City Museum. Considering their exceptional abundance and high quality in Nadin, as well as the lack of an elaborate figural narrative that differentiates them instantly from the morphologically akin belt buckles recovered from the Iapodean, Daorsian, Labeatan and Issaean cultural regions, we suggest distinguishing these specific objects into a special type – Nadin.